Hydromechanical coupling model for mechanical and hydraulic behavior of fractured rock mass in the framework of advanced general particle dynamics. Issue 12 (5th September 2022) - Zhou, Xiaoping; Fan, Xiaowei; Du, Erbao; Bi, Jing; Berto, Filippo
Abstract: In this paper, hydromechanical coupling model is proposed to study the mechanical and hydraulic behavior of fractured rock mass in the framework of advanced general particle dynamics (GPD), and the relationship between stress and seepage is determined. Then, the proposed model is employed to investigate one‐dimensional seepage, and the numerical seepage field is in a good agreement with the analytical solution, implying the feasibility and accuracy of advanced GPD method. Finally, the proposed model is applied to analyze the mechanical and hydraulic behavior of surrounding rock mass around excavated tunnel under hydromechanical coupling conditions, and the numerical results obtained by the proposed model are in a good agreement with those obtained by PFC, which further verifies the correctness of the proposed model.